THE INFLUENCE OF LOCAL GOVERNMENT CHARACTERISTICS ON DISTRICT/CITY GOVERNMENT PERFORMANCE IN CENTRAL JAVA - Febrian Febrian; Shinta Permata Sari (STKIP NU Kabupaten Tegal, 2023)
Government performance is a form of the level of achievement of results from activities or tasks in accordance with the responsibilities that have been given in achieving the goals of an organization. The level of efficiency and effectiveness of local government administration needs to be improved. In addition, a systematic monitoring, evaluation and performance measurement system is needed to measure the progress of local governments within a predetermined time. This study aims to analyze the effect of regional size, level of regional wealth, level of regional dependence, regional spending and audit findings of the Supreme Audit Agency (BPK) on the performance of district/city regional governments throughout Central Java in 2017-2019, obtaining a sample of 105 data , with one data outlier. The results showed that capital expenditure, level of wealth and regional size had an effect on local government performance, while the level of regional dependence and audit findings had no effect on the performance of district/city regional governments throughout Central Java in 2017-2019.